Barbados : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2003)
This paper presents key findings of the Financial System Stability Assessment for Barbados, including Reports on the Observance of Standards and Codes on Monetary and Financial Policy Transparency, Banking Supervision, Securities Regulation, Insurance Regulation, Corporate Governance, and Payment Systems. Systemic risks in the financial sector are generally contained, although the sector faces considerable challenges. Repercussions of the recent economic recession on the banking system are being felt, and profitability and asset quality are likely to be depressed in the near term.